Investigating the influence of probiotics in preventing Traveler's diarrhea: Meta-analysis based systematic review - Basmah F. Alharbi; Abeer A. Alateek (Travel Medicine and Infectious Disease, 2024)
Introduction: Approximately 10–40 million travelers get Traveler's Diarrhea (TD) yearly. A significant decrease in TD incidence has not been achieved by depending solely on antibiotic prophylaxis and educational initiatives. Using prebiotics to prevent TD has also not been examined in previous evaluations of probiotics for TD, which failed to consider the strain-specificity of probiotic efficacy. This review investigates the overall effects of probiotics on preventing TD, including the impact of dosage, duration, and age. Methods: Standard literature databases were searched without restriction on publication year or language. The following criteria are included: randomized controlled trials (RCTs) in English or non-English unrestricted to publication year, excluding animal and observational studies. This systematic review applied the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Results: Of the 166 screened papers, 10 RCTs were included. Lactobacillus acidophilus showed no efficacy in preventing TD except when mixed with other strains. Other genera of lactobacilli showed a protection rate of up to 39% against TD. Similarly, Saccharomyces cerevisiae and Saccharomyces boulardii have been effective in preventing TD. Conclusion: Studies investigating probiotics as a preventive measure for TD remain limited. Only a few probiotics that reduce TD risk exist. Based on this systematic review and meta-analysis, specific probiotic strains, including L. acidophilus, L. rhamnosus, L. fermentum, S. cerevisiae, and S. boulardii, may prevent TD. The effect of additional probiotic strains on TD prevention must be further investigated.